Laccase catalyzed synthesis of iodinated phenolic compounds with antifungal activity. - Julian Ihssen; Mark Schubert; Linda Thöny-Meyer; Michael Richter (PLoS ONE)
Iodine is a well known antimicrobial compound. Laccase, an oxidoreductase which couples the one electron oxidation of diverse phenolic and non-phenolic substrates to the reduction of oxygen to water, is capable of oxidizing unreactive iodide to reactive iodine. We have shown previously that laccase-iodide treatment of spruce wood results in a wash-out resistant antimicrobial surface. In this study, we investigated whether phenolic compounds such as vanillin, which resembles sub-structures of softwood lignin, can be directly iodinated by reacting with laccase and iodide, resulting in compounds with antifungal activity. HPLC-MS analysis showed that vanillin was converted to iodovanillin by laccase catalysis at an excess of potassium iodide. No conversion of vanillin occurred in the absence of enzyme. The addition of redox mediators in catalytic concentrations increased the rate of iodide oxidation ten-fold and the yield of iodovanillin by 50%. Iodinated phenolic products were also detected when o-vanillin, ethyl vanillin, acetovanillone and methyl vanillate were incubated with laccase and iodide. At an increased educt concentration of 0.1 M an almost one to one molar ratio of iodide to vanillin could be used without compromising conversion rate, and the insoluble iodovanillin product could be recovered by simple centrifugation. The novel enzymatic synthesis procedure fulfills key criteria of green chemistry. Biocatalytically produced iodovanillin and iodo-ethyl vanillin had significant growth inhibitory effects on several wood degrading fungal species. For Trametes versicolor, a species causing white rot of wood, almost complete growth inhibition and a partial biocidal effect was observed on agar plates. Enzymatic tests indicated that the iodinated compounds acted as enzyme responsive, antimicrobial materials.